Design of Reverse Osmosis Water Treatment Unit Using Lanxess Lewaplus2 - Al-zobai, Khalid M. Mousa; Ahmed, Saad Ali (Al-Nahrain Journal for Engineering Sciences, 2025)
Basrah is the richest town and the economic capital of Iraq. It suffers from lack of drinking water. This project is a dream to supply drinking water to Basrah citizens within WHO standards. Water should pass sedimentation and filtration stages before interring reverse osmosis unit. The design is carried out using lewaplus2 software. Several parameters should be selected in the design step membrane type, number of stages, number per element in each stage, and the recovery percentage. An optimization is carried out using Minitab ver. 18 for the acceptable limit of TDS and minimum cost and it was found that the optimum conditions were 52% for first stage, the numbers of vessels are 20 for both the first and second stage. In addition, results showed that the pressure and the total dissolved solid increase with increasing the recovery while parameters like the feed flow rate per vessel, the power, and the cost are decreasing with the recovery. Mathematical model described the cost was conducted and statistical study was also done to ensure the results.